Democratización y transición en Chile - Ricardo Yocelevsky (Perfiles Latinoamericanos, 1999)
This examination of the current political situation in Chile seeks to bring to light the deepest and most decisive characteristics of the democratic structure that replaced the dictatorship as of 1990. Specifically it linhs the actions andpositions of thepolitical party elite in the transitionprocess with some of theproblema and limitations in the democratizing procesa, which some political actom in the government are starting to take note of. The author underlines the limitations that the ideological evolution of these actom in the procesa place on the examination of these problema.